Reduciing Risk Mekong Improving Yield in the Drawdown Area of Yali Reservoir, Vietnam - Tran Duc Toan; Nguyen Duy Phuong; Nguyen Dug Dung; Senaratna Sellamuttu, Sonali; Chu Thai Hoanh; Joffre, Olivier M.; Gia Tan Dat; Din, Y. (CGIAR Challenge Program on Water and Food, 2013)
Under the MK1 project Soils and Fertilizers Research Institute (SFRI) and Department of Agriculture and Rural Development (DARD) introduced a short term variety of cassava (KM 98-7) that can reach maturity after 7 months and give better yield and starch content. The on-farm pilot started with 3 farmers in 2012 (1.5 ha) in 1 commune and thereafter expanded to 36 farmers in 2013 (20 ha) in two communes around Yali reservoir. The results in both 2012 and 2013.